2021
DOI: 10.3390/biology10111102
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response in Crayfish Is Species-Specific and Exhibits Changes along Invasion Range of a Successful Invader

Abstract: Immunity is an important component of invasion success since it enables invaders’ adaptation to conditions of the novel environment as they expand their range. Immune response of invaders may vary along the invasion range due to encountered parasites/microbial communities, conditions of the local environment, and ecological processes that arise during the range expansion. Here, we analyzed changes in the immune response along the invasion range of one of the most successful aquatic invaders, the signal crayfis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 131 publications
(180 reference statements)
0
3
0
Order By: Relevance
“…It is notable that the virus is present in crabs at the northern edge of their geographic range. Microbiome community changes and emergence of novel pathogens have been widely reported during the dispersal of host invasion and extension range (Engering et al, 2013;Dragičević et al, 2021). The extensive poleward expansion of C. sapidus in its native range along the western Atlantic and its successful invasion to European waters (Johnson, 2015;Mancinelli et al, 2021), made C. sapidus a well-suited model to study virus evolution, diversity, and viral ecology of marine animals during host habitat expansion and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that the virus is present in crabs at the northern edge of their geographic range. Microbiome community changes and emergence of novel pathogens have been widely reported during the dispersal of host invasion and extension range (Engering et al, 2013;Dragičević et al, 2021). The extensive poleward expansion of C. sapidus in its native range along the western Atlantic and its successful invasion to European waters (Johnson, 2015;Mancinelli et al, 2021), made C. sapidus a well-suited model to study virus evolution, diversity, and viral ecology of marine animals during host habitat expansion and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…This is favorable behavior that is conducive to the invasion of crayfish [ 62 ]. Successful invasion by crayfish has been reported to be influenced by their immunity [ 63 ]. Although we found that their immunity reduced under drought conduction, there was no significant influence on their survival ( Figure S3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The upstream section of the studied river segment passes through a sparsely populated rural region, while the downstream section flows through the industrial zone of the city of Karlovac. Additionally, differences in water temperature were recorded along this part of the watercourse: in a previous study by [ 38 ], the water temperature at the upstream river segment was 5.6 °C lower than at the downstream segment. Apart from the different environmental conditions, the study area also includes sites that differ in crayfish community composition: dense intraspecific populations of signal crayfish (located in the center of the studied area, U2 and D1; Table 1 ), and less abundant heterospecific populations of signal crayfish and narrow-clawed crayfish (located at the edges of the studied area; U1 and D2; Table 1 ) [ 36 ].…”
Section: Methodsmentioning
confidence: 99%